(3GdYbO GdKejf aj JGQjN GdHdO GdCejfs - (3Jbi GdOjf eMeO Hf eMeO Hf CMeO Hf Ydj GdMSfj GdaGSi Gdecj,J (B832 (3g` s ((3OGQ GdfOhI s)
(3ChdgG (B:s
(3jHJOF Hef CSeg (B" (3YJGH(B" s
(3BNQgG (B:s
(3hjfJgi HfgGjI GdcJGH s
(3GdehLhO efg GdKdK GdKGdK hgh GdCNjQs
(3QGLY HbjI CLRGA gPG GdcJGH ai GdbSe GdChd ef GdagQSJ HQbe (B333s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B331 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B300s
Keywords: (3GdJGQjNs